Undiagnosed autism in the elderly- autism vs schizophrenia - Naumovska, Andromahi; Bonevski, Dimitar (My University, 2022)
Autism was identified in the 1940s, but wasn’t widely recognized until the 1970s. This means some older autistic adults may have never have received a diagnosis. It can also be difficult to diagnose ASD in an older person because certain symptoms can mirror other age related conditions. Conditions that impact how the brain functions, such as dementia may mask certain autistic traits. Being less mobile, and a shrinking social circle can also impact an older person’s social communication skills – which again could mask underlying autism. Older people can also be more susceptible to certain mental health problems, particularly loneliness and depression. This can have a knock on effect self-esteem and behavior, and cause people to avoid social situations. This study was conducted with a goal make differentiation between autism and schizophrenia in older people in North Macedonia.
Keywords: autism; schizophrenia